Answer:
UH HOLD ON RIGHT QUICK CAN YOU TELL ME THE QUESTION
Step-by-step explanation:
A) I included a graph, look below.
B)
Input the y in x = y + 3.
x = (-4x - 3) + 3
x = -4x + 0
Add 4x to both sides.
5x = 0
Divide both sides by 5.
x = 0
Input that x value in y = -4x - 3
y = -4(0) - 3
y = 0 - 3
y = -3
(0, -3)
C)
Convert both equations to Standard Form.
x = y + 3
Subtract y from both sides.
x - y = 3
y = -4x - 3
Add 4x to both sides.
4x + y = -3
Add the equations together.
4x + y = -3
x - y = 3
equals
5x = 0
Divide both sides by 5.
x = 0
Input that into one of the original equations.
0 = y + 3
Subtract 3 from both sides.
-3 = y
(0, -3)
The answer is f^-1(x)=8/3+x/3
The reflected points would be (-3,-7)
The x coordinate would stay the same but the y-coordinate would be the opposite
All you have to do is follow PEMDAS (if you don't know what that is, search it up).
-2-5(4n-6)=-132
Distribute the 5 to everything in the parentheses.
-2-20n+30= -132
Combine like terms.
-20n+28 = -132
Subtract 28 from both sides.
-20n = -160
Divide by -20 on both sides.
n = 8